Impact of Cu/W rate on thermal properties, crystal structure and microstructure of NiTiCuW shape memory alloys - Tatar, Cengiz; Taze, Alev; Kok, Mediha (Springer Heidelberg, 2024)
In this study, the composition-dependent properties of a new type of NiTiCuW shape memory alloy were investigated. The martensite transformation temperature was measured by differential scanning calorimetry, crystal structure by XRD, microstructure analysis by microhardness measurement and scanning electron microscopy. The increase in Cu/W ratio in the composition decreased the transformation temperature below room temperature, and the alloys are in austenite phase at room temperature. X-ray results also supported the thermal measurement results. Moreover, a difference in the microhardness values of NiTiCuW alloys was observed, which exhibited martensite phase and austenite phase at room temperature.
Keywords: Phase transformation; Shape memory; W; Calorimetry; Hardness